William Gilmore Simms correspondence - Simms, William Gilmore, 1806-1870.
Twenty-three ALsS (1842-1850) written by Simms to George Frederick Holmes, two ALsS (1859 July 26 and 1860 April 14) from Simms to John Esten Cooke, and one ALS (1866 October 2) from Simms to Thomas Addis Emmet.
Poet and author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Cooke, John Esten, -- 1830-1886 -- Correspondence; Emmet, Thomas Addis, -- 1828-1919 -- Correspondence; Holmes, George Frederick, -- 1820-1897 -- Correspondence; Authors; Poets